KESALAHAN PELAFALAN DALAM KETERAMPILAN BERBICARA BAHASA JERMAN SISWA SMA NEGERI 3 LAMONGAN - LESTARI, SEMILIR (LATERNE, 2017)
German is a Foreign language lessons in high school. Learning a foreign language is not just skilled speaking, but also need to be Pronunciation, because pronunciation is important. If within pronunciation error occurred then happened also changes meaning. The research was conducted to obtain types mistake pronunciation and factors. The purpose of this study is described the types of fault its pronunciation and Describes the factors causing the error of pronunciation in German. The type of research this is the qualitative study. The data source of this research is students of SMA Negeri 3 Lamongan class XI Semester 1 Which consisted of 18 people. Furthermore the technique used is random technique and engineering data collection in this research using a test oral focused on pronunciation. Matter used themed family life obtained from the teaching books in the process of learning the language of germans , and the text in the form of text descriptive. The data analysis is done by recording, then transcribed. From the transcript results can be known where the error and determine the type of mistakes made by students. Of this research , students are still facing difficulty in pronouncing vocabulary german. The location of mistakes made by students happened to phoneme / ei / as many as 11 people, a mistake on the phoneme /ch/ as many as 7 people, a mistake on the phoneme /ä/ as many as 6 people, a mistake on the phoneme /eu/as many as 7 people, and a mistake on the phoneme /sch/ as many as 5 people. Based on the results of the study, types a fault committed by students included in the mistake phonetics which includes a mistake pronunciation or of writing and the causes of error occurrances is learning strategy students itself. Keywords : error, pronunciation, German speaking skills